Sustainability Reporting Practices - the Case of Bank Millennium - Masztalerz, Marek (Studia Oeconomica Posnaniensia, 2017)
The purpose of this paper is to analyse the sustainability reporting practices of Bank Millennium, and to answer the question of what and how it is re-ported and presented in those reports. The adopted research method consists of the content analysis of nine of Bank Millennium's sustainability reports for the years 2006-2014. The paper presents the features and the content of the Bank's sustainability reports, and the choice (what is measured and reported?) and presentation forms (tabular of graphical?) of numbers in those reports?